PROMISE, FULFILLMENT, AND ISRAEL: TESTING A BIBLICAL-THEOLOGICAL FRAMEWORK OF CHRIST AND THE KINGDOM OF GOD - Edhi Prasetyo; Simon Stefanus Baitanu (STT Bethel Indonesia Jakarta, 2026)
This article explores the theological relationship between Christology, the Kingdom of God, and Israel within the framework of biblical and systematic theology. Employing a qualitative–exegetical method combined with constructive theological reflection, it examines how New Testament Christology integrates the identity and mission of Jesus with God’s covenant promises to Israel. The study argues that Jesus, as the Messiah from the line of David, fulfills Israel’s hope for the Kingdom of God and extends it to all nations without negating Israel’s theological significance. It demonstrates that authentic Christology is rooted in God’s reign, grounded in the covenant with Israel, and revealed through the ministry of Jesus, who manifests the presence of God’s Kingdom in human history. The research further emphasizes that the contemporary Church is called to live out a Kingdom-oriented spirituality that is inclusive, ethical, and missional, while acknowledging Israel as a sign of God’s enduring faithfulness in salvation history. Consequently, the integration of Christ, the Kingdom, and Israel offers a coherent biblical-theological paradigm that reinforces the unity between divine promise and fulfillment in Christ for all nations.